Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1016/j.janxdis.2012.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Avoidant personality disorder in individuals with generalized social anxiety disorder: What does it add?

Abstract: Avoidant Personality Disorder (AvPD) has a high level of symptom overlap and comorbidity with Generalized Social Anxiety Disorder (GSAD). We examined whether the presence of comorbid AvPD adds significant clinically relevant information for individuals seeking treatment for GSAD. Results suggested that AvPD was significantly associated with poorer quality of life and greater disability in univariate, but not multivariate analyses. Endorsement of more AvPD symptoms was associated with increased disability, incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 31 publications
0
28
0
1
Order By: Relevance
“…Individuals with avoidant PD, which is often associated with interpersonal dysfunction, often report having difficulties with being assertive and are socially inhibited (Cummings et al, 2013). Avoidant PD has a high symptom similarity with generalized social anxiety disorder and on a continuum may represent a more severe form of social anxiety disorder (Marques et al, 2012). Social anxiety and associated symptoms have been found to be more associated with women than with men (Hofmann et al, 2010;Kuusikko-Gauffin et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Individuals with avoidant PD, which is often associated with interpersonal dysfunction, often report having difficulties with being assertive and are socially inhibited (Cummings et al, 2013). Avoidant PD has a high symptom similarity with generalized social anxiety disorder and on a continuum may represent a more severe form of social anxiety disorder (Marques et al, 2012). Social anxiety and associated symptoms have been found to be more associated with women than with men (Hofmann et al, 2010;Kuusikko-Gauffin et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies indicate qualitative differences between SAD and AvPD (Hummelen, Wilberg, Pedersen, & Karterud, 2007; Huppert, Strunk, Ledley, Davidson, & Foa, 2008; Lampe & Sunderland, 2015). For instance, AvPD may include an aspect of emotional guardedness towards other people that is not well captured by the SAD construct (Marques et al, 2012), and family studies suggest that AvPD may be related to the schizophrenia-spectrum (e.g., Fogelson et al, 2010). There is no consensus on the issue of qualitative differences between the disorders (Bernstein, Arntz, & Travaglini, 2015).…”
mentioning
confidence: 99%
“…The similarity between these disorders has been extensively discussed in the literature (Rettew, 2000; Widiger, 1992). Although Avoidant PD has been found to reflect a higher severity of social inhibition and impairment in some studies (Hummelen, Wilberg, Pedersen, & Karterud, 2007; Turner, Beidel, Dancu, & Keys, 1986), specifically regarding the Avoidant PD criterion involving emotional guardedness (Marques et al, 2012), other researchers have reported only minimal differences (Ralevski et al, 2005). In addition, both disorders have been found to share the same genetic liability (Reichborn-Kjennerud, 2007).…”
Section: Discussionmentioning
confidence: 99%